Association Between Age, Body Mass Index, and Iron Deficiency Anemia Among Libyan Children - Haloom Elhashmi; Fatma Aldarat (AlQalam Journal of Medical and Applied Sciences, 2026)
Nutritional deficiencies in children can be reflected in growth parameters, such as body weight, height, and Body Mass Index (BMI). Iron Deficiency Anemia (IDA) is the most common nutritional deficiency manifested in various BMI categories. Aim: The present study evaluated the association between age, BMI, and iron deficiency anemia among Libyan children. An observational retrospective study was conducted at the pediatric hematology clinic, Benghazi Medical Center, Libya, from December 1, 2019, to December 31, 2024. This study of 128 Libyan children aged 2-16 years with low iron status collected data including demographic parameters (age and sex), and hemoglobin and serum ferritin were recorded, and anthropometry (weight, height, and BMI), and three nutritional anthropometric categories (healthy weight, underweight, and overweight). We assess the association between ag, IDA, and BMI. The data were analyzed using SPSS 27.0, and the statistical significance level was considered as 0.05. The rate of IDA is 66.4%, and age ≥12 years had the highest proportion of IDA, with a statistically significant association between age group and IDA (χ² = 14.155, p = 0.001), and the majority (70%) of IDA children had normal BMI (healthy weight). However, there is no statistically significant association between BMI category and IDA (χ² = 1.274, p = 0.529). A healthy weight was most common among 12- to 16-year-olds, with a statistically significant association between age group and BMI category (χ² =10.300, p = 0.036). Our study shows no association between BMI and IDA. Iron deficiency anemia is more common among healthy children. This study emphasizes the necessity of screening for IDA, irrespective of the nutritional status, especially in the risk age group, teenagers, preschoolers, and adolescents.